PALLIATIVE-CURATIVE SURGICAL INTERVENTIONS IN GASTRIC CANCER PATIENTS WITH LIVER METASTASES - R.Z. YULDOSHEV; D.Z. ZIKIRY AKHODZHAEV; M.T. RAKHMATOV; S.A. DILSHODOV; YO.I. AZ ATULLOEV; A.A. KHODZHAMKULOV (Паёми Сино, 2018)
Objective: To assess the effectiveness of relatively curative surgical interventions in the treatment of patients with gastric cancer with metastases to the liver and to show the role of active surgical tactics in improving the quality of life of patients.